THE INFLUENCE OF SELF EFFICACY AND LOCUS OF CONTROL ON EMPLOYEE PERFORMANCE WITH OCB AS AN INTERVENING VARIABLE (CASE STUDY AT THE JEMBER DISTRICT TRANSPORTATION SERVICE) - Subagiono, Yoyok; Martini G, Ni Nyoman Putu; Zakiyyah, Amalina Maryam (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This research aims to determine the influence of self-efficacy and locus of control on employee performance with OCB as an intervening variable (case study at the Jember Regency Transportation Service). Method: This research uses the Explanatory Research type. The population in this study were all employees of the Jember Regency Transportation Service, totaling 202 employees. Researchers used a saturated sample method where all members of the population were sampled. The data analysis method used in this research is Structural Equation Modeling (SEM). Results: The research results show that the higher Self Efficacy will increase Performance, the higher Locus of Control will increase Performance, the higher Self Efficacy will increase OCB, the higher Locus of Control will increase OCB, and the higher OCB will increase Performance. Novelty: Self Efficacy has a positive and significant impact on structural employee performance through OCB. Locus of Control has a positive and significant impact on structural employee performance through Organizational Citizenship Behavior.